ANALISIS DAMPAK CARBON TAX TERHADAP KINERJA KEUANGAN PERUSAHAAN: STUDI KASUS PADA PT. INDOCEMENT TUNGGAL PRAKARSA TBK - Primardiningtyas, Filzah; Adyatma, Rafi; Putri Shamaya, Veren; Yovita R Pandin , Maria (LPPM Universitas Bina Bangsa, 2025)
The purpose of this research is to determine the impact of carbon tax implementation on the financial performance of PT Indocement Tunggal Prakarsa tbk. This study uses a descriptive qualitative method. The result of this research is that the implementation of the Carbon Tax on PT Indocement Tbk will affect the company's financial performance. With the implementation of the carbon tax, the amount of profit will also decrease because the profit will be used to pay the carbon tax of PT Indocement Tunggal Prakarsa Tbk. The decrease in the company's profit will affect the financial performance of PT Indocement Tunggal Prakarsa Tbk. This will impact the ratios of PT Indocement Tunggal Prakarsa Tbk such as the ROA and ROE ratios. In 2023, the ROA of PT Indocement Tunggal Prakarsa Tbk was 6.57% and the ROE was 9.30%.